2015
DOI: 10.1002/cnm.2700
|View full text |Cite
|
Sign up to set email alerts
|

A computational fluid dynamics comparison between different outflow graft anastomosis locations of Left Ventricular Assist Device (LVAD) in a patient‐specific aortic model

Abstract: Left ventricular assist devices (LVADs) are mechanical supports used in case of heart failure. Little is known as the height of the anastomosis in aorta might influence the hemodynamic. The aim of the study was to evaluate the fluid dynamic behavior due to the outflow graft placement of a continuous flow LVAD in ascending aorta and to identify the insertion site with the best hemodynamic profile. Computational fluid dynamic studies were carried out to analyze 4 different anastomosis locations in a patient-spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 36 publications
4
35
0
Order By: Relevance
“…[7][8][9][10] However, previous studies using CFD have only reported blood flow analysis in the ascending aorta without the aortic root because of the complex anatomy of the aortic root and its components such as the aortic valve, coronary arteries, and Valsalva sinus. [11][12][13][14][15] To evaluate the three-dimensional blood flow in the aortic root, three-dimensional patient-specific geometries with accurate anatomy of the aortic root were reproduced using electrocardiogram-gated 320-slice computed tomographic (CT) images. 16 We hypothesized that the blood flow pattern in the ascending aorta in patients with LVAD with AI is different from that in patients with LVAD without AI, and that the angle and position of anastomosis of the outflow graft with the ascending aorta affect the retrograde blood flow pattern in the aortic root.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] However, previous studies using CFD have only reported blood flow analysis in the ascending aorta without the aortic root because of the complex anatomy of the aortic root and its components such as the aortic valve, coronary arteries, and Valsalva sinus. [11][12][13][14][15] To evaluate the three-dimensional blood flow in the aortic root, three-dimensional patient-specific geometries with accurate anatomy of the aortic root were reproduced using electrocardiogram-gated 320-slice computed tomographic (CT) images. 16 We hypothesized that the blood flow pattern in the ascending aorta in patients with LVAD with AI is different from that in patients with LVAD without AI, and that the angle and position of anastomosis of the outflow graft with the ascending aorta affect the retrograde blood flow pattern in the aortic root.…”
Section: Introductionmentioning
confidence: 99%
“…Reduced pressure and lower WSS in the ascending aorta were observed under pulsatile flow LVADs versus continuous flow LVADs. Caruso et al reported that the height of the anastomosis could change the aortic hemodynamic states [ 6 ], and the outflow graft, placed 2 cm above the ST junction, achieved the most favorable hemodynamic states. Similarly, Yang et al demonstrated that a large increase in wall shear stress is found near the cannular during LVAD support [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that under pulsatile flow LVADs support, lower WSS and reduced pressure in ascending aorta was achieved. Caruso et al [4] studied the effect of the height of the anastomosis on the aortic hemodynamic states. The results suggested that the placement of the outflow graft at 2 cm above the ST junction gave the most favorable hemodynamic profile.…”
Section: Introductionmentioning
confidence: 99%